The Effect of Providing Psychoeducation on Stress Levels of Patients with Type II Diabetes Mellitus - Fatmawati; Haryanti Haris; Jusniati (Comprehensive Health Care, 2023)
Psychoeducation is an action that is given to individuals and families as a way to deal with difficulties in mental changes through the provision of information related to simple psychology or other information that affects people's welfare. This study aims to determine the effect of psychoeducation on the stress level of type II DM patients in the Working Area of ​​the Caile Public Health Center, Bulukumba Regency. This type of research is a type of quantitative research. The design of this study used the "Pre Experiment One Group Pretest-Posttes design.” Sampling was carried out by purposive sampling method with a total sampling technique. The research sample taken was 30 people from the total population of type II DM patients who experienced stress in the Work Area of ​​the Caile Public Health Center, Bulukumba Regency. The measuring tool used is a questionnaire. The results of this study found that out of 30 type II DM patients who experienced stress levels before being given psychoeducation, the stress level of type II DM patients was in the moderate category, namely 28 people (93.3%), and after being given psychoeducation the stress level was in the moderate category. decreased to 16 people (53.3%). From the results of the Wilcoxon test, it was found that the value of p (0.001) < α (0.05), the result was that "There is an effect of providing psychoeducation on the stress level of type II DM patients in the Work Area of ​​the Caile Public Health Center, Bulukumba Regency. Researchers hope that health workers can create a psychoeducation program as a tool to reduce stress levels in type II DM patients in the working area of ​​the Caile Public Health Center, Bulukumba Regency.